2009
DOI: 10.1093/nar/gkp426
|View full text |Cite
|
Sign up to set email alerts
|

Transcripts of unknown function in multiple-signaling pathways involved in human stem cell differentiation

Abstract: Mammalian transcriptome analysis has uncovered tens of thousands of novel transcripts of unknown function (TUFs). Classical and recent examples suggest that the majority of TUFs may underlie vital intracellular functions as non-coding RNAs because of their low coding potentials. However, only a portion of TUFs have been studied to date, and the functional significance of TUFs remains mostly uncharacterized. To increase the repertoire of functional TUFs, we screened for TUFs whose expression is controlled durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 69 publications
2
57
0
Order By: Relevance
“…It is claimed that several non-coding named transcripts related to hMSC differentiation (TMDs) display distinct transcriptional kinetics during hMSC adipogenesis and/or osteogenesis. 36 Using Microarray or RNA Profiling technology, some studies showed that various lncRNA transcripts are functioning in adipogenesis. 11,37 However, there are extremely few investigations on how food affects lncRNA expression during lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is claimed that several non-coding named transcripts related to hMSC differentiation (TMDs) display distinct transcriptional kinetics during hMSC adipogenesis and/or osteogenesis. 36 Using Microarray or RNA Profiling technology, some studies showed that various lncRNA transcripts are functioning in adipogenesis. 11,37 However, there are extremely few investigations on how food affects lncRNA expression during lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…These steps were repeated twice with an interval of 1 wk. We also tested the adipogenic and osteogenic potential of perichondrocytes as previously described (37).…”
Section: Methodsmentioning
confidence: 99%
“…For example, XIST is named for “X (Inactive)-Specific Transcript” (16,17), while DANCR stands for “Differentiation Antagonizing Non-Protein Coding RNA” (1820). However, when IncRNAs are initially identified without a known function, they are named based on the associated genomic context or assigned an arbitrary name based on the GENCODE categorization, which divides IncRNAs into the following sub-categories (21,22):

Antisense: IncRNA whose sequence overlaps the exonic sequence of a protein-coding gene on the opposite strand (e.g., HIF1a-AS1 )

lincRNA: IncRNA located within the intergenic regions of protein-coding genes (e.g., LINC00152 )

Sense-overlapping: IncRNA whose intronic sequences encode a protein-coding or noncod-ing gene without overlap of exonic sequences (e.g., SOX2-OT )

Sense intronic: IncRNA residing within introns of a coding gene (e.g., SPRY-IT1 )

Processed transcript: IncRNA that does not contain an ORF and does not fit in any of the above categories

…”
Section: Incrnas: Nomenclature and Categorizationmentioning
confidence: 99%